Analysis of The Influencer Marketing, Ratings and Customer Reviews on Purchasing Decisions - Mulyati, Sri; Putriani, RDN Dwi; winanti, winanti; Goestjahjanti, Francisca Sestri; Marusaha, Tiardo Jonathan; Farhan, Akhmad; Mendrofa, Yeremia; Kumoro, Dwi Ferdiyatmoko Cahya; Himmy’azz, Istajib Kulla; Purno, Marhaendro (Journal of E-business and Management Science, 2024)
There are still many companies that do not pay attention to the importance of influencer marketing, ratings and customer reviews due to ignorance and low understanding. This research underlines the importance of marketing strategies that combine influencer marketing with positive interactions from customers and good product reputation to influence consumer purchasing decisions effectively, so researchers are interested in conducting research entitled The Influence of Influencer Marketing, Ratings and Customer Reviews on Purchasing Decisions. With the research variables that will be analyzed are influencer marketing X1, Rating X2, Customer Review the research results can be seen from the multiple correlation level value of 0.745, this shows that the correlation level has a strong influence. The coefficient of determination value is 0.809, meaning that the Influencer Marketing, Rating and Customer Review variables have an influence on purchasing decisions of 80.9% and the remaining 19.1% is influenced by other variables not examined in this research. Meanwhile, the results of simultaneous hypothesis testing show a significant effect because Fcount > Ftable (129,801 > 3,090).